Metformin extended-release versus metformin immediate-release for adults with type 2 diabetes mellitus: A systematic review and meta-analysis of randomized controlled trials. (August 2021) - Abrilla, Aedrian A.; Pajes, A. Nico Nahar I.; Jimeno, Cecilia A.
Highlights: Metformin extended-release (MXR) is marketed as more tolerable than conventional metformin immediate-release (MIR). Lowering of HbA1c, but not serum glucose, statistically worsened versus MIR. Lipid control, except LDL-C lowering, statistically worsened versus MIR. Among adverse events, only dyspepsia was statistically improved versus MIR. MXR is clinically similar in glycemic control but minimally improves tolerance compared to MIR. Abstract: Aim: To compare the efficacy and tolerability of metformin extended-release (MXR) and the conventional metformin immediate-release (MIR) formulations in adults with type 2 diabetes mellitus (T2DM) Methods: PubMed, the Cochrane Library, ClinicalTrials.gov and other sources were searched until 19 March 2021 for randomized controlled trials (RCTs) that compared equal daily doses of MXR and MIR in adults with T2DM. Random-effects model meta-analysis was performed to obtain pooled mean difference (MD) of change from baseline for continuous outcomes and risk ratio (RR) for dichotomous outcomes. Primary outcomes considered were HbA1c and key gastrointestinal (GI) symptoms (abdominal discomfort or pain, diarrhea, dyspepsia, and nausea & vomiting). Results: Nine RCTs that randomized a total of 2609 adults revealed that MIR was statistically associated with better HbA1c lowering (MD 0.09% [95% confidence interval or CI, 0.01%, 0.17%]), MXR only reduced dyspepsia (RR 0.58 [95% CI, 0.34, 0.98]), and both formulations were associated with similar cumulative incidence of other key GI symptoms. Conclusions: MXR was associated with statistically worse but likely clinically similar HbA1c lowering and minimal improvement of GI intolerance compared to MIR. Protocol Registration: PROSPERO (CRD42019148008).